American Women in Science: 1950 to the Present - Julia Gelfand (Issues in Science and Technology Librarianship, 1999)
This article reviews the book American Women in Science: 1950 to the Present. Santa Barbara, CA: ABC Clio, 1998, by Martha J. Bailey.